A High-Calorie Diet Aggravates Mitochondrial Dysfunction and Triggers Severe Liver Damage in Wilson Disease Rats - Einer, Claudia; Leitzinger, Christin; Lichtmannegger, Josef; Eberhagen, Carola; Rieder, Tamara; Borchard, Sabine; Wimmer, Ralf; Denk, Gerald; Popper, Bastian; Neff, Frauke; Polishchuk, Elena; Polishchuk, Roman S.; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2019)
BACKGROUND & AIMS: In Wilson disease, ATP7B mutations impair copper excretion into bile. Hepatic copper accumulation may induce mild to moderate chronic liver damage or even acute liver failure. Etiologic factors for this heterogeneous phenotype remain enigmatic. Liver steatosis is a frequent finding in Wilson disease patients, suggesting that impaired copper homeostasis is linked with liver steatosis. Hepatic mitochondrial function is affected negatively both by copper overload and steatosis. Therefore, we addressed the question of whether a steatosis-promoting high-calorie diet aggravates liver damage in Wilson disease via amplified mitochondrial damage.
CRIS-Team WoS Importer:2019-05-03